abs(2x+5)=6x+23

Simple and best practice solution for abs(2x+5)=6x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for abs(2x+5)=6x+23 equation:


Simplifying
abs(2x + 5) = 6x + 23

Reorder the terms:
abs(5 + 2x) = 6x + 23
(5 * abs + 2x * abs) = 6x + 23
(5abs + 2absx) = 6x + 23

Reorder the terms:
5abs + 2absx = 23 + 6x

Solving
5abs + 2absx = 23 + 6x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Reorder the terms:
-23 + 5abs + 2absx + -6x = 23 + 6x + -23 + -6x

Reorder the terms:
-23 + 5abs + 2absx + -6x = 23 + -23 + 6x + -6x

Combine like terms: 23 + -23 = 0
-23 + 5abs + 2absx + -6x = 0 + 6x + -6x
-23 + 5abs + 2absx + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
-23 + 5abs + 2absx + -6x = 0

The solution to this equation could not be determined.

See similar equations:

| 0=-0.4x^2+16x+90 | | 3(2H-14)=4(H-5) | | 8S+6=-18 | | 2(A+6)=10 | | 3E-4=E+16 | | 8-T=56+11T | | 6X+6=7X+9 | | 10-3I=-17 | | 5K-2=2K+10 | | 5(2D+1)=35 | | ln(128)-7ln(2)= | | log(128)-7log(2)= | | 2-7x+5=13-3x | | ln(2x)-ln(4x)= | | ax-b=bx-a | | 3y^2+8y-3=0 | | 4k+11=36 | | 1250g= | | -2x+15=30-0.5x | | 0.5x=2x-45 | | x=30-0.5x | | 3(2s-3)=-(7-s) | | f-8-3f=3-7+4 | | 4x-1.2=x | | -3x+4=6-x | | 53b+43y= | | 3x+4=6-x | | 2x+0.2= | | abx+aby=a^2+b^2 | | (ax-by)=2b | | 2a-3=8(a+1)+13a+9 | | -15=x-5 |

Equations solver categories